Ferromagnetism at room temperature in activated graphene oxide - Raj, K. Govind; Joy, Pattayil Alias (Chemical Physics Letters, 2014)
High room temperature ferromagnetic moment with high Curie temperature (>700 K) for graphene oxide (GO) is obtained by a simple chemical activation using phosphoric acid followed by heat treatment at 800 degrees C. The field and temperature variations of the magnetization data indicate ferromagnetic, paramagnetic and diamagnetic contributions in the acid/heat treated sample. IR spectroscopic studies suggest hydrogenation (reduction) of GO after the acid and heat treatments. The results point to the role of defects, extent of hydrogenation, changes in the bonding characteristics and the nature of the functional groups in determining the different magnetic contributions. (C) 2014 Elsevier B.V. All rights reserved.

Magnetism in disordered carbon as a function of the extent of graphitization - Raj, K. Govind; Joy, Pattayil Alias (Solid State Communications, 2014)
Magnetic properties of disordered carbon have been investigated as a function of the extent of graphitization. It is found that the magnetization of the disordered carbon decreases with increasing degree of graphitization. Treatment with acid modifies the magnetic characteristics considerably and the original magnetic characteristics are retained upon further heat treatment. The results show that the intrinsic magnetic behavior of the disordered carbon depends on the microstructure and that the edge states play a critical role in deciding the magnetic interactions in the amorphous carbon system. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Amorphous carbon; disordered carbon; Graphitization; magnetic properties